Variation and Trends in Anaphylaxis Care in United States Children's Hospitals. (13th April 2016) - Michelson, Kenneth A.; Monuteaux, Michael C.; Neuman, Mark I.
Abstract: Objectives: We sought to determine the extent of variation in treatment of children with anaphylaxis. Methods: We identified children 1 month to 18 years of age presenting with a primary diagnosis of anaphylaxis to one of the 35 pediatric hospitals included in the Pediatric Health Information System between January 1, 2009, and September 30, 2013. We evaluated the variation in use of β2 agonists, glucocorticoids, histamine‐1 (H1) antagonists, histamine‐2 (H2) antagonists, inhaled epinephrine, intravenous fluids, and oxygen. We assessed whether variation exists in the rates of hospitalization and 3‐day emergency department (ED) revisits and whether a temporal trend exists in the ED visit rate for anaphylaxis. Results: Among 10, 351 children with anaphylaxis, the hospital‐level median use of common anaphylaxis therapies varied for β2 agonists (22%, interquartile range [IQR] = 16%–26%), glucocorticoids (71%, IQR = 65%–76%), H1 blockers (60%, IQR = 57%–65%), H2 blockers (53%, IQR = 36%–64%), inhaled epinephrine (2.2%, IQR = 1.3%–3.5%), intravenous fluids (26%, IQR = 13%–41%), and oxygen (2.6%, IQR = 0.8%–4.1%). Hospitalization rates ranged from 12% to 95%, with a median rate of 41%. Anaphylaxis diagnoses rose from 5.7 to 11.7 patients per 10, 000 ED visits between 2009 and 2013 (p < 0.001 for trend). Conclusions: There is substantial variability in the use of common therapies and hospitalization rates for children cared for in U.S. children's hospitals. Additionally, ED visits for children with anaphylaxis are increasing at U.S. children's hospitals. These findings highlight the need for research defining optimal care for anaphylaxis.